Dinamika Pemikiran Ekonomi Islam di Indonesia: Menakar Prinsip Bisnis dalam Pemikiran Adiwarman Karim dan Dawam Rahardjo - Fauzi Abdul Azis; Syahrial (MUAMALAH: Journal of Islamic Economics and Business Law, 2026)
The rapid growth of the Islamic economic industry in Indonesia has often been met with academic criticism regarding the imbalance between legal formality and the substance of social justice. This study aims to analyze this dynamic by comparing the construction of business principles from two of the most influential Islamic economic thinkers in Indonesia: Adiwarman Azwar Karim and M. Dawam Rahardjo. Using qualitative methods with a library research approach and content analysis, this study examines the primary works of both figures to map their epistemology, main principles, and business orientation. The results show significant paradigmatic differences. Adiwarman Karim represents a legal-formal approach that emphasizes the validity of contracts, the prohibition of MAGHRIB (Maysir, Gharar, Riba), and the concept of Economic Value of Time. His approach is top-down, focusing on strengthening financial institutions and Sharia compliance. In contrast, M. Dawam Rahardjo promotes a substantive-philosophical approach based on the Social and Economic Monotheism of the Constitution. For Rahardjo, business principles must be bottom-up, with an orientation toward empowering the people's economy, anti-monopoly, and distributive justice, transcending mere sharia labels. This study concludes that the tension between Karim's formalism and Rahardjo's substantialism is not a mutually exclusive conflict, but rather a complementary spectrum. Indonesia's Islamic economic ecosystem requires a synthesis of both: Karim's thinking is necessary to build the operational foundation and legal certainty of the industry, while Rahardjo's thinking is crucial as a moral compass to prevent business practices from becoming trapped in peci-wearing capitalism. This synthesis is an absolute prerequisite for the development of contemporary business models that are both professional and socially impactful.